PREDIKSI NILAI KARBON YANG HILANG AKIBAT KEBAKARAN HUTAN DAN LAHAN DI KOTA BANJARBARU - Niken Larasati Kusuma Dini; Ahmad Jauhari; Normela Rachmawati (Jurnal Sylva Scienteae, 2022)
Forests can maintain climate stability in the long term, vegetation in the forest can convert carbon dioxide (CO2) into Oxygen (O2). Forest and land fires produce plant vegetation and the addition of gas CO2 in the atmosphere, this can inhibit the carbon cycle in the atmosphere so that it can cause climate change. The purpose of this research is to estimate the area of forest and land fires in Banjarbaru City and carbon emissions from the burned area in Banjarbaru City. Determination of the location based on the distribution of hotspots in Banjarbaru City in 2018. In estimating the area of fire and land using the Normalized Burn Ratio (NBR) method. From the area affected by the fire, the estimated burnt carbon emissions were calculated using the Greenhouse Gas Inventory Implementation Method Vol 3, then the results obtained showed that the burned area using the NBR method had an accuracy value of 47.06%. The burned area resulting from this method was 0.43 Ha of old secondary forest, 3.51 Ha of medium secondary forest, 52 Ha of old plantation and young secondary forest and 240.95 Ha of shrubs. From the burned area, the CO2 emission values for each land cover were 11.27 tons/ha in old secondary forest, 28.28 tons/ha in medium secondary forest, 241.97 tons/ha in young secondary forest and 952.39 tonnes/ha on scrubHutan dapat menjaga kestabilan iklim dalam waktu jangka panjang, vegetasi yang berada pada hutan dapat merubah karbondioksida (CO2) menjadi O2. Kebakaran hutan dan lahan mengakibatkan hilangnya vegetasi tumbuhan serta penambahan gas CO2 di atmosfer, hal ini dapat menghambat siklus karbon pada atmosfer sehingga dapat menyebabkan perubahan iklim. Tujuan dari penelitian untuk mengestimasi luas area kebakaran hutan dan lahan di Kota Banjarbaru dan emisi karbon dari luas area yang terbakar di Kota Banjarbaru. Penentuan lokasi penelitian berdasarkan sebaran hotspot Kota Banjarbaru Tahun 2018. Dalam mengestimasi luas area kebakaran hutan dan lahan menggunakan metode Normalized Burn Ratio (NBR). Dari luas daerah yang mengalami kebakaran kemudian dihitung estimasi emisi karbon terbakar menggunakan metode Pedoman Penyelenggaraan Inventarisasi Gas Rumah Kaca Vol 3. Hasil yang diperoleh menunjukan bahwa luas area terbakar memiliki nilai akurasi 47,06 %.  Luas areal terbakar pada hutan sekunder tua 0,43 Ha, hutan sekunder sedang 3,51 Ha, perkebunan tua dan hutan sekunder muda 52 Ha dan semak belukar 240,95 Ha. Dari luas area yang terbakar di peroleh nilai Emisi CO2 pada masing-masing tutupan lahan sebesar 11,27 ton/ ha pada Hutan sekunder tua, 28,28 ton/ha pada hutan sekunder sedang, 241,97 ton/ha pada hutan sekunder muda dan 952,39 ton/ha pada semak belukar